Designing a children’s health exposomics study protocol: The CHILDREN_FIRST multi-country prospective cohort using multi-omics and personalized prevention approaches - Corina Konstantinou; Georgia Soursou; Samuel Abimbola; Pantelis Charisiadis; Angelos Kyriacou; Theofano Modestou; Michalis Tornaritis; Charalambos Hadjigeorgiou; Agapios Agapiou; Efstathios A. Elia; George Milis; Alexis Kyriacou; et al. (PLoS ONE, 2026)
Non-communicable diseases (NCDs) account for ~71% of all deaths globally, including 15 million premature deaths each year (deaths between 30–69 years of age). Instead of waiting until disease manifestation, focusing on the origins of NCDs during childhood offers a critical window of disease prevention and control. The CHILDREN_FIRST international cohort observatory study aims to investigate how the spatio-temporal evolution of the children’s exposome profiles in the Mediterranean region influences early-life programming of chronic disease risk during the critical window of susceptibility in primary school years (6–11 years of age). The study protocol adopts the human exposome framework integrated with a personalized prevention approach, using multi-omics platforms and advanced machine learning algorithms implemented across Mediterranean countries, namely Cyprus, Greece, and Albania. The cohort will consist of children enrolled in the first grade of primary school, who will undergo annual follow-up assessments until completion of primary education. During the annual assessments, children’s exposome parameters from the three main exposome domains will be evaluated using different assessment types, i.e., molecular biomarkers of exposure/effect, sensors, and questionnaires. Standardized biospecimen and data collection methods will be employed following harmonized standardized operating procedures. The reference model of Observational Medical Outcomes Partnership – Common Data Model (OMOP-CDM) developed and maintained as part of the Observational Health Data Sciences and Informatics (OHDSI) initiative will be used to conduct federated data analysis. This CHILDREN_FIRST study protocol is a human exposome-based initiative to establish a long-term prospective cohort infrastructure for biomedical research on children’s health in the Mediterranean region. The cohort’s exposome-based findings will systematically feed into the evaluation and design of chronic disease prevention programs. Expected results would inform evidence-based policy making and the development of health interventions for reducing the risk of NCDs in childhood and later in adult life.